How does typeface familiarity affect reading performance and reader preference - Beier, Sofie; Larson, Kevin (Information Design Journal, 2013)
Some typographers have proposed that typeface familiarity is defined by the amount of time that a reader has been exposed to a typeface design, while other typographers have proposed that familiarity is defined by the commonalities in letter shapes. These two hypotheses were tested by measuring the reading speed and preferences of participants. Participants were tested twice with common and uncommon letter shapes, once before and once after spending 20 minutes reading a story with the font. The results indicate that the exposure period has an effect on the speed of reading, but the uncommon letter shapes did not. Readers did not like the uncommon letter shapes. This has implications for the selection of type and the design of future typefaces.